2023
DOI: 10.1111/bjop.12661
|View full text |Cite
|
Sign up to set email alerts
|

Preparing children to cope with earthquakes: Building emotional competence

Abstract: Natural disasters, including earthquakes, can have a traumatic impact on children's psychological wellbeing and development. The efficacy of interventions aimed at enhancing children's socio‐emotional learning has been documented in the literature. At the same time, these techniques are the key for training children for possible future disasters by enhancing their knowledge about behavioural preparedness and emotional competence. However, research on evidence‐based training programs on earthquakes combining di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 153 publications
(180 reference statements)
1
13
0
Order By: Relevance
“…Previous research has demonstrated the value of using psychoeducation as a way to empower people's knowledge in relation to risk management, with increased awareness recognized by the United Nations as a pillar for improving children and adolescents' readiness towards disasters, rather than supporting people's natural recovery (Howard & Goelitz, 2004;Seddighi et al, 2020;Torani et al, 2019). Coherently with this, we documented a rise in children's knowledge and metacognitive awareness about how to cope with earthquakes through an evidence-based psychoeducational programme combining traditional and digital activities (Raccanello et al, 2023c). Such intervention was based on a theoretical model focussing on the psychological processes characterizing the responses to disasters (Raccanello et al, 2023c).…”
Section: Disaster-related Interventions For Children and Adolescentssupporting
confidence: 62%
See 4 more Smart Citations
“…Previous research has demonstrated the value of using psychoeducation as a way to empower people's knowledge in relation to risk management, with increased awareness recognized by the United Nations as a pillar for improving children and adolescents' readiness towards disasters, rather than supporting people's natural recovery (Howard & Goelitz, 2004;Seddighi et al, 2020;Torani et al, 2019). Coherently with this, we documented a rise in children's knowledge and metacognitive awareness about how to cope with earthquakes through an evidence-based psychoeducational programme combining traditional and digital activities (Raccanello et al, 2023c). Such intervention was based on a theoretical model focussing on the psychological processes characterizing the responses to disasters (Raccanello et al, 2023c).…”
Section: Disaster-related Interventions For Children and Adolescentssupporting
confidence: 62%
“…Coherently with this, we documented a rise in children's knowledge and metacognitive awareness about how to cope with earthquakes through an evidence-based psychoeducational programme combining traditional and digital activities (Raccanello et al, 2023c). Such intervention was based on a theoretical model focussing on the psychological processes characterizing the responses to disasters (Raccanello et al, 2023c).…”
Section: Disaster-related Interventions For Children and Adolescentsmentioning
confidence: 76%
See 3 more Smart Citations